PENERAPAN MODEL MASTERY LEARNING DALAM MENINGKATKAN PENGUASAAN KOMPETENSI DASAR MATEMATIKA SISWA SEKOLAH DASAR - Annisa (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2026)
This study aims to analyze the implementation of the Mastery Learning model in improving the mastery of basic mathematics competencies among elementary school students. The background of this research is based on the low level of students’ understanding of fundamental mathematical concepts, which affects their learning outcomes. The Mastery Learning model is chosen because it emphasizes learning completeness through structured instruction, sufficient learning time, and continuous feedback and remedial activities until students achieve mastery standards. The research method used is Classroom Action Research (CAR), conducted in two to three cycles, each consisting of planning, implementation, observation, and reflection stages, with elementary school students as the research subjects. Data were collected through learning outcome tests, student activity observation sheets, and documentation, and analyzed using descriptive quantitative and qualitative approaches. The results show that the implementation of the Mastery Learning model significantly improves students’ mastery of basic mathematics competencies, as indicated by the increase in students’ average scores and the percentage of learning mastery in each cycle, along with improved student learning activities reflected in more active participation in the learning process. In conclusion, the Mastery Learning model is effective in improving elementary school students’ mastery of basic mathematics competencies and can be used as an alternative student-centered learning strategy to achieve optimal learning outcomes.